Еволюція збалансованої зовнішньої політики Азербайджану з 2003 року - Гурбанов, Рауф (Науково-теоретичний альманах Грані, 2025)
Relevance. Azerbaijan’s geopolitical position at the crossroads of Europe and Asia, and its rich energy resources, have placed it at the center of regional and global interest. Since 2003, Azerbaijan has pursued a balanced foreign policy aimed at maintaining constructive relations with both Western and Eastern power centers. In the context of increasing geopolitical rivalry, regional conflicts, and shifting global alliances, the country’s ability to maintain diplomatic balance while safeguarding national interests has become especially significant. The relevance of this topic lies in its potential to contribute to the understanding of how small and mid-sized states can maneuver within a complex international system without aligning rigidly with one geopolitical bloc. Furthermore, studying Azerbaijan’s foreign policy evolution provides valuable insights into regional stability, post-conflict diplomacy, and energy geopolitics in the South Caucasus. Since 2003, Azerbaijan has pursued a balanced foreign policy to strengthen its regional and global role. This period witnessed significant geopolitical changes, influenced by rising energy capacity, growing transit potential, regional conflicts, and global power competition. Navigating these dynamics, Azerbaijan maintained constructive relations with global and neighboring powers, aiming to protect national interests and ensure long-term stability. From 2003 to 2010, the focus was on regional cooperation, large-scale energy infrastructure (like the BTC pipeline), and enhanced security. The country carefully balanced its relations with the West, Russia, and Iran, avoiding alignment with any single bloc. Between 2010 and 2016, Azerbaijan adopted a more flexible diplomatic stance. It played an active role in international forums and supported peaceful efforts regarding the Karabakh conflict, emphasizing sovereignty and territorial integrity. The 2016–2023 phase brought more assertive foreign engagement. The 2020 Second Karabakh War marked a turning point. Post-war, Azerbaijan prioritized reconstruction, regional connectivity, and pragmatic diplomacy. It pursued a multi-vector approach, maintaining equilibrium between actors like Turkey, Russia, the EU, and China. Findings suggest this balanced strategy safeguarded Azerbaijan’s independence and enhanced its international reputation. By leveraging its strategic location and energy resources, Azerbaijan emerged as a reliable, stable partner. The purpose of this article is to examine the evolution of Azerbaijan’s balanced foreign policy from 2003 to 2023 by dividing it into three major periods: 2003–2010, 2010–2016, and 2016–2023. Each of these periods represents shifts in Azerbaijan’s strategic priorities, external environment, and internal capacities. The article seeks to analyze how Azerbaijan has adjusted its foreign policy tools and alliances in response to regional developments, security challenges, and global transformations. The study aims to provide a systematic and comprehensive understanding of Azerbaijan’s foreign policy trajectory, evaluating the consistency of its balanced approach and its impact on national interests and regional positioning.